Improving Students' Speaking Ability by Using Puppet Craft - Ramadhan; Eli Nofriati (Journal of English Education and Social Science, 2022)
The purpose of this study was to improve students' speaking skills through Puppet Craft Media. This research was conducted with the aim of overcoming the problems encountered in the classroom, namely: students are not interested in speaking English. For data collection, the writer chose a speaking test, a checklist for observation, and a questionnaire. The writer and collaborator applied it to find out the improvement of students speaking ability by introducing themselves in English in each cycle. Through a questionnaire, researchers can find out whether Puppet Craft media can overcome problems in speaking English or not. Research requires 2 cycles. The subjects of this study were 23 students in first grade at SMPN 1 JULI in the 2021/2022 academic year. In the first cycle, the average percentage value obtained is 65.2% and this is classified as the average student agreeing to use Puppet Craft as a medium to improve speaking in English. In the second cycle, the average value of the percentage of students increased, namely the average value of the percentage obtained by students was 71.9%. After analyzing the students' scores, the writer concludes that the students' speaking ability has improved using Puppet Craft as a Media.